Worker Alienation and Compensation at the Savannah River Site. (May 2016) - Ashwood, Loka; Wing, Steve
Corporations operating U.S. nuclear weapons plants for the federal government began tracking occupational exposures to ionizing radiation in 1943. However, workers, scholars, and policy makers have questioned the accuracy and completeness of radiation monitoring and its capacity to provide a basis for workers' compensation. We use interviews to explore the limitations of broad-scale, corporate epidemiological surveillance through worker accounts from the Savannah River Site nuclear weapons plant. Interviewees report inadequate monitoring, overbearing surveillance, limited venues to access medical support and exposure records, and administrative failure to report radiation and other exposures at the plant. The alienation of workers from their records and toil is relevant to worker compensation programs and the accuracy of radiation dose measurements used in epidemiologic studies of occupational radiation exposures at the Savannah River Site and other weapons plants.